Determination of Iron Chelating Agents by Analytical Methods: A Review. (3rd May 2020) - Malik, Aamir; Firke, Sandip D.; Patil, Ravindra R.; Shirkhedkar, Atul A.; Surana, Sanjay J.
Abstract: Acute iron poisoning and chronic iron overload consequences in significant morbidity and mortality worldwide. Treatment of acute iron poisoning and chronic iron overload can be challenging and care providers are often tackled with management dilemmas. Iron chelating agents are commonly prescribed for patients with iron deficiency anemia. In this review article, different analytical techniques are reported used for qualitative and quantitative analysis of iron chelating agents like, deferiprone, deferoxamine, and deferasirox. Efforts are taken to collect all related articles published till October 2018. This review discusses all analytical methods, its advantages and disadvantages as well as its applications. This article will help you to know about basic analytical techniques as well as advanced hyphenated techniques practiced for determination of iron chelating agents in different matrices. The techniques discussed in this review follow the ICH guidelines for method validation.